Somatotopic organization in rat striatum: evidence for a combinational map. - Brown, L L (1992)
2-Deoxy-D-[14C]glucose autoradiography was used in awake rats to map neural activity in the sensorimotor sector of striatum. Stimulation of hindlimb, trunk, or forelimb activated primary sensory cortex in a localized columnar pattern, indicating activation of somatosensory receptors and a discrete cortical functional unit. In sensorimotor striatum, an image analysis detection technique revealed regions of maximal activity, or features, that formed a patchy pattern of activation reminiscent of the known anatomic patterns of cortico-striate terminals. Ipsilateral as well as contralateral activation was observed. The activated areas revealed a body map in striatum that was organized in a manner consistent with cortical topography (dorsoventrally: hindlimb, trunk, forelimb) at most anteroposterior levels, similar to that found in other species. However, at other levels, a different organization (e.g., trunk, hindlimb, forelimb) was observed. Furthermore, the arrangements of body region and side were also unique at different anteroposterior levels. Thus, functional activity showed multiple, different juxtapositions of body elements--i.e., a combinational map. The data suggest that striatum may provide an anatomic substrate for different combinations of inputs necessary to select and integrate movement.